Pengaruh Kepribadian (Personality) dan Keinginan Untuk Bertindak (Intention to Act) Terhadap Perilaku Tanggung Jawab Lingkungan (Responsible Environmental Behavior) Siswa - I Made Putrawan; Diana Vivanti Sigit; Tiara Agustiani Mahardika (IJEEM - Indonesian Journal of Environmental Education and Management, 2021)
Environmental damage is intentionally done by individuals or groups of people. Understanding of environmental education involves various parties including one of them students. Behavior of responsibility possessed by students is supported by the personality and desire to act in dealing with environmental problems. This study was aimed at finding effect personality and intention to act toward responsible environmental behavior students. Research conducted at SMAN 31 Jakarta on the Semester I of 2019/2020 school year. The method used is a survey method through causal studies and analyzed by path analysis. The research instruments used were responsible environmental behavior (27 items, reliability 0.763), personality (26 items, reliability 0.820), and intention to act (30 items, reliability 0.904). The results showed that personality has a direct effect on the intention to act, intention to act has a direct effect on responsible environmental behavior , personality has a direct effect on responsible environmental behavior, and the results of intention to act are suitable as mediating variables between personality and responsible environmental behavior on students. Keys : Student, Personality, Intention to Act, Responsible Environmental Behavior, Reliability.